Molecular evidence for Anaplasma phagocytophilum in Ixodes ricinus from Turkey - Aktas, Munir; Vatansever, Zati; Altay, Kursat; Aydin, M. Fatih; Dumanli, Nazir (Elsevier Science Inc, 2010)
This study investigated the presence of the pathogen Anaplasma phagacytophilum in ixodid ticks removed from humans living in three provinces (Giresun, Trabzon, Rize) in the east of the Black Sea Region of Turkey. A total of 1097 ixodid ticks were examined for the presence of A. phagocytophilum DNA. From the 95 pooled tick samples tested, species-specific fragments of A. phagocytophilum (11/95 samples, 11.6%) were amplified by nested PCR. Adult Ixodes ricinus (9/53 samples, 17.0%) and Ixodes spp. nymphs (2/9 samples, 22.2%) were infected with A. phagocytophilum. None of the remaining tick species gave a positive result for the presence of the pathogen. All nested PCR-positive samples were directly sequenced. The partial sequences (457 bp) of the amplicons obtained from the infected tick pools were 100% identical to one another and to previously isolated sequences from human patients. To obtain a longer 16S rRNA gene sequence, one representative sample was reamplified with the universal primer set. The longer representative sequence (1306bp) also shared 99.92% similarity (a single adenine deletion) with the recently reported complete sequence of A. phagocytophilum. (c) 2009 Royal Society of Tropical Medicine and Hygiene. Published by Elsevier Ltd. All rights reserved.
Keywords: Ixodes; Anaplasma phagocytophilum; Nested PCR; DNA sequence analysis; 16S rRNA; Turkey